Experimental analysis of combustion performance of biodiesel absorbed pellets in a domestic boiler. (15th June 2020) - Sungur, Bilal; Topaloğlu, Bahattin
Abstract: Wood pellets gain increasing importance as an alternative and renewable fuel. In this study, biodiesel absorbed pellets were used, which is a new method for usage of pellet fuels. In this way, the naturally existing pores in pellets are filled with biodiesel, which improves the combustion properties compared to untreated (raw) pellets. Raw and biodiesel absorbed pellets were burned in a domestic experimental boiler to analyse comparatively the combustion characteristics such as thermal power, efficiency and flue gas emissions. Additionally, the absorption capacity of pellet fuels was investigated. Flue gas temperature and emissions (CO2, O2, CO, SO2 and NOx ) were measured in the chimney. Combustion efficiencies were calculated and compared with each other. Experiments were performed without any modifications to the boiler, which was set for raw pellet combustion. By the usage of biodiesel absorbed pellets, the thermal power input increased from 15.2 kW to 20.9 kW (nearly 37.5% more), whereas the thermal efficiency increased from 91.7% to 93%. The average flue gas temperature was about 89.6 °C and nearly 13 °C higher than raw pellet fuel. By biodiesel absorbed pellet, significantly more CO and slightly less NOx emission concentrations in flue gases were obtained. Highlights: A new method of using pellet fuels by absorbing biodiesel is presented. Raw pellet absorbed nearly 17% biodiesel on mass basis. Biodiesel-enriched pellets increased the heating value about 37.5% on volume basis. Using biodiesel absorbed pellet increased the thermal efficiency from 91.7% to 93%. Biodiesel absorption led to higher CO and lower NOx concentrations in exhaust gases.